Råne River Geochemistry - Conrad, Sarah (Luleå University of Technology, 2024)
This dataset contains element concentrations of quantitative element screenings (ICP-MS, 70+ elements), conducted on filtered water samples and the filtered material (cut-off 0.22 μm) from samples taken in the Råne River and in the Råne River estuary during three sampling campaigns (2013, 2014, and 2016). The purpose of the study was to observe changes in the dissolved and particulate element concentrations during spring flood and along a slowly increasing salinity gradient.

Water samples in the Råne River estuaries were collected during the spring flood in February, March and April 2014, in May and June 2013, and in May, June and July 2014. Water samples from the Råne River estuaries were taken from the coastguard vessel KBV005 in May and June 2013. Samples at all sampling stations were collected at 0.5, 5 and 10 meters deep if they were deep enough. At the sampling in March 2014, samples were taken from the first three stations in the estuaries while they were still covered with ice. In 2014, the tests were carried out through a hole in the ice. The hole was drilled with an ice drill and the samples pumped up from depths of 0.5, 5 and 10 meters.
Water samples from the Råne River were collected during the spring flood 2016, from March to July. In Råneälven, at the sampling station Orrbyn, samples were taken from a bridge in the middle of the river.

Dessa datafiler innehåller elementkoncentrationer av kvantitativa elementanalyser (ICP-MS, 70+ element), utförda på filtrerade vattenprover och det filtrerade materialet (cut-off 0,22 μm) från prover tagna i Råneälven och Råneälvens mynning under tre provtagningskampanjer (2013, 2014, och 2016). Syftet med studien var att observera förändringar i lösta och partikelformiga elementkoncentrationer under vårflod och längs en långsamt ökande salthaltsgradient.

Vattenprover togs i Råneälvens mynningar under vårfloden i februari, mars och april 2014, i maj och juni 2013, samt i maj, juni och juli 2014. Vattenproverna från Råneälvens mynningar togs från kustbevakningsfartyget KBV005 i maj och juni 2013. Proverna från samtliga provtagningsstationer togs på 0.5, 5 och 10 meters djup om de var tillräckligt djupa. Vid provtagningen i mars 2014 togs prover vid de tre första stationerna när mynningarna fortfarande var istäckta. Under 2014 genomfördes proverna genom ett hål i isen. Hål borrades med en isborr och proverna pumpades upp från 0,5, 5 och 10 meters djup.
Vattenprover togs i Råneälven under vårflod 2016, från mars till juli. I Råneälven, vid provtagningsstationen Orrbyn, togs prover från en bro mitt i ån.
Råneälvens geokemi
Keywords: GEOCHEMISTRY; GEOCHEMICAL PROPERTIES; environmental chemistry; miljökemi; chemistry; kemi; environmental chemistry; natural science; environmental chemistry; salinity gradient; salthaltsgradient; Natural Sciences; Naturvetenskap; Chemical Sciences; Kemi; Analytical Chemistry; Analytisk kemi; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Environmental Sciences; Miljövetenskap; Geochemistry; Geokemi; Environment; Miljö